Revitalitas Nilai-Nilai Pendidikan Islam Dalam Membentuk Karakter Siswa di Era Digital - Rahman, David; G, Gusmaneli; Hidayat, Samsul (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The development of technology in the digital era has a significant impact on the behavior and mindset of students. In this context, the revitalization of Islamic educational values is an urgent need to shape the character of students who have noble morals and integrity. Islamic education based on the teachings of the Qur'an and Hadith contains values such as honesty, responsibility, discipline, and social concern that are very relevant to the challenges of the times. This study aims to explore the strategic role of Islamic educational values in shaping students' character amidst the influence of a digital culture that tends to be free and permissive. Through a descriptive qualitative approach and literature study, it was found that the consistent application of Islamic values in the educational environment can be a moral fortress for students. This revitalization effort requires synergy between families, schools, and communities in internalizing Islamic values through role models, strengthening the curriculum, and using technology wisely. Thus, Islamic education has a vital role in shaping a generation that is spiritually, emotionally, and socially intelligent in the digital era.